Vitrectomy with Fovea-Sparing Internal Limiting Membrane Peeling for Myopic Foveoschisis - Seppey, C.; Wolfensberger, T. J. (Klinische Monatsblätter für Augenheilkunde, 2017)
Background Myopic foveoschisis is a rare form of a tractional maculopathy, which occurs in patients with elevated axial length. The contraction of the posterior hyaloid exerts tangential traction on the retinal surface with a subsequent continuous splitting of the retinal layers. Internal limiting membrane (ILM) peeling has been advocated in foveoschisis, but it has been associated with post-operative macular hole formation. We report on a modified surgical technique, which spares the fovea and may reduce the risk for macular hole formation. Methods Retrospective analysis of 6 patients with myopic foveoschisis. The mean age was 53.8 ± 12.9 years (4M, 2F) and mean myopia was − 18.3 ± 6.5 Dpt. After a 23 g pars plana vitrectomy, the ILM was peeled on the entire macular surface, except in the foveal region lest the thin foveal structures be damaged. All patients received a gas tamponnade with 23 % SF6 and maintained a face down position for 5 days. Results Mean best-corrected pre-operative visual acuity was 0.87 ± 0.56 logMAR, which increased to 0.60 ± 0.40 logMAR at the end of follow-up. The retinal thickness, as measured by optical coherence tomography, decreased from 799 ± 352 micrometers to 318 ± 60 micrometers at the end of follow-up 7.8 ± 5.7 months. No case developed a macular hole. Conclusions Vitrectomy with fovea sparing ILM peeling is a promising surgical technique, which results in an improved foveal anatomy and retinal function. Due to the sparing of the fovea, this surgical technique may reduce the risk of macular hole formation in the post-operative period.
Keywords: high myopia; myopic foveoschisis; tractional maculopathy